Fundamentals of Entrepreneurship (ENT 300) : Case study Barong Tinuk / Abg Alauddin Abg Marzuki @ Abg Saperi … [et al.] - Abg Marzuki @ Abg Saperi, Abg Alauddin; Sofian, Nurul Izati; Japri, Iqmal Fashreen Anthasha; Zulkipli, Mohamad Nazrie; Nasaruddin, Nur Nadia Shamiera; Tarang, Palissa Nain (2018)
Barong Tinuk known as one of the great restaurant that serves unique taste of Melanau's dishes. Linut, umai, ayam tinuk and ikan tinuk are the customer's favourite dishes when the customer come to have dinner with their beloved family. Barong tinuk well-used the Facebook as their promoting platform which help the customer to recognise their restaurant better.